2019
DOI: 10.1515/sjpain-2018-0308
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of women with chronic pelvic pain referred to physiotherapy treatment after multidisciplinary assessment: a cross-sectional study

Abstract: Abstract Background and aims Chronic pelvic pain (CPP) in women is a complex condition that can seriously impact health and quality of life. Clinical guidelines for CPP place great demands on healthcare professionals, as they require both specialized knowledge about the pelvic area and knowledge of the mechanisms of chronic pain. To ensure best possible assessment and treatment of these women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…We also found high levels of anxiety (59.5% had level of SA and 49.2% of TA in the percentile range 75–99). In studies in which self-applied scales are used to assess anxiety and depression in women with CPP, high percentage of anxiety and depressive symptoms were found [ 9 , 55 , 56 , 57 , 58 ]. In one study that measured the intensity of anxiety and depression, they found moderate or severe anxiety in 40% and 13.1% respectively, and moderate-to-severe depression in 22.3% and 4.6% [ 9 ], similar to our findings; although we found a higher percentage of severe symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…We also found high levels of anxiety (59.5% had level of SA and 49.2% of TA in the percentile range 75–99). In studies in which self-applied scales are used to assess anxiety and depression in women with CPP, high percentage of anxiety and depressive symptoms were found [ 9 , 55 , 56 , 57 , 58 ]. In one study that measured the intensity of anxiety and depression, they found moderate or severe anxiety in 40% and 13.1% respectively, and moderate-to-severe depression in 22.3% and 4.6% [ 9 ], similar to our findings; although we found a higher percentage of severe symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…When male partners conclude they have little influence over their partner's condition, this can exacerbate a sense of powerlessness and frustration, possibly leading to the depressive symptoms that have been reported by male partners in previous studies. 15,16 For some of the couples in our study, family and friends were a source of support in a difficult situation. For others, there was little support available in their social network, either because they did not dare disclose their problems to anyone or because those around them showed little understanding.…”
Section: Discussionmentioning
confidence: 98%
“…In the meantime, their psychological well-being is undermined 10 as they struggle with sexuality, relationships, self-esteem and identity, [10][11][12][13] as well as depression, anxiety and suicidality. 6,14 Male partners to women with vulvodynia also tend to suffer from anxiety and depression symptoms 15,16 as well as sexual dysfunction. 17 These partners are often the only people in the women's lives who see how much the pain is affecting them.…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted in Brazil with 91 women, pain intensity varied according to body mass from 2.66 to 3.15 28 . In another study conducted in Norway, 108 women with CPP participated and the average pain intensity assessed was 4,2 30 . The moderate pain intensity observed may justify the use of different analgesic methods reported by the participants.…”
Section: Discussionmentioning
confidence: 99%